Study on the Flood Risk Under Climate Change in the XeChamphone Sub-watershed - Phetaoi, Khamlar; Vongphachanh, Sinxay; Kasyoudoum, Vilakone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Lao PDR is a country experiences floods almost every year, which is mainly caused by climate change and storms. During the years of 1990-2018, 72% of the population had affected by flooding. The XeChamphone sub-watershed is affected by floods every year and increases more and more violence. Therefore, the purpose of this study is: 1) to simulate stream flow for the XeChamphone sub-watershed (using the data of 2019) and estimate the future stream flow (years of 2050 and 2075) and 2) to assess the flood area mapping. This study, HEC-HMS model is applied to analyze and predict stream flow under observed rainfall and precipitation from the regional climate model (RCM) and the flood risk maps is developed using integrated HEC-RAS and ArcGIS. The results of the study show that the HEC-HMS model can simulate the stream flow in XeChamphone sub-watershed very well based on the model performance index values such as R2 = 0.88 and NSE = 0.87 which are within the standard threshold or acceptable values. In 2019, there is a maximum average flow equal to 1,036.8 m3/s in September and the average flow rate for the whole year was 175.7 m3/s; In the future (2050 and 2075) the maximum average flow equal to 1,295.1 m3/s and 1,240.5 m3/s in July and the average annual flow rate is equal to 344.3 m3/s and 319.6 m3/s respectively. In 2019, there are flood areas covering 20% of the total water catchment area and flood areas with severe level or damage level covering 5.90%; in 2050, there will be 31% of flooded areas and 10.39% of severely flooded areas; in 2075, there is a flood area covering 26% and a flood area at a severe level covering 8.05%. When comparing the amount of water flow and the area at risk of flooding in the past and the future, it is seen that the amount of water flow and the area at risk of flooding in the future tend to increase higher than in the past and the amount of water flow in 2050 may be higher than 2075.This study analyzes the amount of water flowing into the watershed in the past and the future under no land use change; The analysis of the trend of the amount of water flowing into the catchment in the future is only 02 years and the assessment of the flood risk area at this time has not yet calculated the factor of the speed of the flood; Mapping the risk of future floods with land use data in 2019 is assumed to be under land use without change and this research process can be used to estimate the stream flow and assess areas flood risk areas in other catchments that have similar geographical and climatic conditions to the XeChamphone sub-watershed.